Tribological performance of wire arc additive manufactured 347 austenitic stainless steel under unlubricated conditions at elevated temperatures. (August 2020) - Duraisamy, R.; Kumar, S. Mohan; Kannan, A. Rajesh; Shanmugam, N. Siva; Sankaranarayanasamy, K.; Ramesh, M.R.
Highlights: Tribological behaviour of AISI 347 substrate and WAAM processed 347 samples at elevated temperatures have been studied. WAAM processed 347 exhibits heterogeneous microstructure along the building direction. The presence of Fe2 O3 and Fe3 O4 at elevated temperatures aided the formation of mechanically mixed composite oxide layer. Wear mechanisms change from adhesive at 200 °C to mild oxidative at 600 °C where glaze oxide layers reduced the wear rate. Abstract: Wire Arc Additive Manufacturing (WAAM) is an effective metal additive manufacturing process. In this research, 347 Austenitic Stainless Steel (ASS) walls were manufactured with ER347 consumable material. The microstructure of the WAAM processed 347 plate is entirely heterogeneous with changing grain morphology along the building direction and this is attributed to the complex cyclic thermal history during WAAM process. The microstructure is composed of columnar, cellular and equiaxed structures at various regions. The hardness decreased gradually from bottom to top along the building direction. The volume fraction of ferrite ranged from 0.5% to 4.2% at various regions and the presence of niobium carbide (NbC) was confirmed. The aim of the current work is to provide an outline of the WAAM processed 347 steel under dry sliding conditions at elevated temperatures. The elevated temperature wear mechanism has mild oxidative wear characteristic due to the formation of tribo-oxides on the wearing and sliding surfaces. However, the average coefficient of friction (COF) is lower for the WAAM processed 347 compared to 347 substrate. In all cases after initial running-in, the wear debris from the wearing and sliding surface forms mechanically mixed composite layer of tribo-oxides (Fe2 O3, Fe3 O4 and Al2 O3 ). The worn surface at 200 °C presents different wear behavior compared to the samples at 400 °C and 600 °C. The wear at 200 °C is a typical adhesive wear, while the wear at 400−600 °C is mild oxidative wear. The increase in the percentage of Fe3 O4 helps to heal the wear surface by forming a mechanically mixed composite layer. The characteristics of mild oxidative wear were elucidated.